Implementasi Nilai-Nilai Aswaja Nahdlatul Ulama dalam Pembentukan Karakter - Rahmania, Nurani; Safitri, Anita Nur (IERA, Islamic Education and Research Academy, 2023)
Education is a basic need that must be met for every individual, group, society and nation and state. Goodeducation is an education based on religious values, so that good character can be formed and can be realized in everyday life. Today there are often problems related to the destruction of the character of the nation. In overcoming this MI Sayid Abdurrahman 2 Pagerwojo applies the values of NU aswaja in the formation of the character of its learners. Penelitian aims to 1) Knowing the values of NU aswaja applied in the formation of the character of learners in MI Sayid Abdurrahman 2 Pagerwojo. 2) Describe the implementation of NU aswaja values in the formation of student character in MI Sayid Abdurrahman 2 Pagerwojo. 3) Describe supporting factors and obstacles in the implementation of NU aswaja values in the formation of student character in MI Sayid Abdurrahman 2 Pagerwojo. This research uses qualitative approaches with descriptive methods. The data collection techniques used are with observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and conclusion withdrawal. Data validity checking techniques are carried out with triangulation and persistence of observations. The results showed that the values of NU aswaja namely ta'awun, tawasuth, i'tidal, tasamuh, tawazun, and amar ma'ruf nahi munkar were implemented in character formation in MI Sayid Abdurrahman 2 Pagerwojo. The implementation of these values is done through methods of understanding, transparency, and habituation. Factors supporting the implementation of NU's aswaja values in character formation in MI Sayid Abdurrahman 2 Pagerwojo are the environment, berasal from the same understanding and the existence of furudhul ainiyahmadrasah program, while theinhibition factor is pergaulan outside madrasah, pnyalah use gadgets, and lack of communication with parents.